Meter placement in power system networka comprehensive review, analysis and methodology - Lekshmana R.; Padmanaban S.; Mahajan S.B.; Ramachandaramurthy V.K.; Holm-Nielsen J.B. (MDPI AG, 2023)
The blackout in North India due to the failure of the central grid has led to the need for intelligent power system state estimation, where optimal location is necessary to understand. State estimation meter placement plays a major role in the smart operation of a modern distributed power system. A literature review of the different algorithms incorporated for the determination of minimal number of meters required for the measurement of real time measurements is presented for the power system and distribution system state estimation, including smart meter location. 2018 by the authors. Licensee MDPI, Basel, Switzerland.